Quality and Benefits of Translation Model of Transfer Text in Foreign Exchange Services Transaction at Bank Negara Indonesia Surakarta - Ipung Sri Purwanti Hery (Trunojoyo University of Madura, 2021)
This is a qualitative descriptive study analyzes the social process in translation model of foreign exchange service texts at Bank Negara Indonesia Surakarta. The analysis is based on Functional Systemic Linguistics, translation principles and banking policies. The objectives are to: (1) examine the translation quality models (2) explore the benefits of translation models, (3) verify the foreign exchange service text in English and Indonesia (4) know the employees’ability toward foreign exchange services (5) reveal the customer’s ability in understanding the transfer transactions. Data are lexicogrammatically system, cohesion and text structure. Samples were taken at Bank Negara Indonesia Surakarta, as it provides overseas services using transaction tools in English and Indonesian texts. The quality of translation is analyzed based on group, lexis, clause, mood structure, theme/rheme and transitivity system; while the benefits of translation is based on tenor enlightening the affect, contact and status; whereas mode focused on channels and media. The findings show that quality of translation model of foreign exchange text is stated very good and useful. It is easily understood by customers who applied foreign exchange transactions at Bank Negara Indonesia Surakarta